Has the decline in the intensity of internal migration been accompanied by changes in reasons for migration? - Kalemba, Sunganani; Bernard, Aude; Corcoran, Jonathon; Charles-Edwards, Elin (My University, 2022)
The last few decades have seen the intensity of internal migration decline in Australia and other advanced economies including the United States. Recent evidence suggests that changes in the composition of the population alone do not account for this persistent downward trend. This has led migration scholars to suspect that more profound behavioural changes driven by social, economic, and technological transformations are at play and that shifts in migration behaviour are likely to be reflected in changes in reasons for migration. We use data from the Household, Income and Labour Dynamics in Australia survey to shed new light on the factors driving the decline in internal migration in Australia between 2002 and 2018. This is done by examining annual trends in self-reported reasons for intrastate and interstate migration and applying a series of pooled logistic regressions. Results reveal a decline across all reasons for migration, and not only employment-related migration contrary to explanations proposed in the extant literature. The decline in employment-related migration does not appear to be the result of a rise in alternative forms of mobility such as teleworking or substitution with inter-industry or occupation mobility. Furthermore, we also find that the negative effect of duration of residence has increased for family-related migration. Collectively, these findings suggest that behavioural change, particularly increased place attachment, may have contributed to the decline in internal migration.
Journal of Population Research
Keywords: Housing, communities and neighbourhoods; Migration and settlement